ChemInform Abstract: Catalytic Enantioselective Synthesis of α‐(Benzylamino)cyclobutanones. Issue 47 (November 2015) - Melis, Nicola; Ghisu, Lorenza; Guillot, Regis; Caboni, Pierluigi; Secci, Francesco; Aitken, David J.; Frongia, Angelo
Abstract: via tandem condensation/intramolecular rearrangement/proton transfer reaction of hydroxycyclobutanone and various secondary amines